GJB2 c.235delC variant associated with autosomal recessive nonsyndromic hearing loss and auditory neuropathy spectrum disorder - Xia, Hong (Genet Mol Biol, 2019)
Autosomal recessive nonsyndromic hearing loss (ARNSHL) is a genetically heterogeneous neurosensory disorder, usually characterized by congenital or prelingual hearing loss. We report a Han Chinese male, born to consanguineous parents, presenting with nonsyndromic sensorineural hearing loss, whose clinical phenotype was also consistent with auditory neuropathy spectrum disorder (ANSD). After exome sequencing, a gap junction protein beta 2 gene (GJB2) c.235delC variant in the homozygous state was detected in the patient. Both parents were heterozygous for this variant, as documented by Sanger sequencing. The known pathogenic GJB2 c.235delC variant was not detected in 200 healthy controls. It is predicted to be a disease-causing alteration by generating a truncated protein p.(L79Cfs*3), disturbing the appropriate folding and/or oligomerization of connexins and leading to defective gap junction channels. This study shows that the association of homozygosity of the GJB2 c.235delC variant with ARNSHL and ANSD in a patient.